Pengaruh Persepsi Harga Produk dan Electronic Word of Mouth Terhadap Kepercayaan Pengguna Aplikasi Tokopedia pada Mahasiswa di Wilayah Semarang - Galuh Meliana Anggraeni; Febby Fariska; Mita Widya Pratama; Khairani Zikrinawati; Zulfa Fahmy (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted to measure the effect of price perceptions and electronic word of mouth on the trust of Tokopedia application users in Semarang city students. This study was conducted by linear regression data analysis techniques and using a quantitative approach through purposive sampling technique with a sample of 113 respondents. Based on the results of the analysis can be argued that the perception of price and electronic word of mouth simultaneously affect the trust of Tokopedia application users with the value of F-count 90,496 with sig < 0.001. Perception of price and electronic word of mouth have a significant positive effect partially on the trust of Tokopedia application users at Semarang City students